エトピリカ (Fratercula cirrhata)から得られたハジラミ類 - OHTA, Sora; 21692; YOSHINO, Tomoo; 21693; SUZUKI, Natsumi; 21694; TOMISAWA, Nami; 21695; ITO, Takaomi; 21696; 浅川, 満彦; 1839; et al. (日本野生動物医学会, 2021)
Article During the postmortem of tufted puffin chicks (Fratercula cirrhata), who died a few days after hatching in the aquarium, a large number of chewing lice were collected. These lice were identified as Quadraceps helgovauki (Philopteridae) based on morphological caracteristics. This is the first record of Q. helgovauki from F. cirrhata and in Japan. 国内水族館で飼育され、孵化後3日で死亡したエトピリカ(Fratercula cirrhata)のヒナの剖検において、多数のハジラミ類が採集された。ハジラミは形態学的にニシツノメドリから報告のある Quadraceps helgovaukiと同定された。本種はエトピリカから初めて記録され、また国内初記録であった。 journal article